The Influence of Superstars on Organizational Identification of External Stakeholders: Empirical Findings from Professional Soccer - Daniel Högele; Sascha L. Schmidt; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2012)
This paper examines the effect of superstars on external stakeholders' organizational identification through the lens of sport. Drawing on social identity theory and the concept of organizational identification, as well as on role model theories and superstar economics, we develop several hypotheses regarding the influence of soccer stars on their fans' degree of team identification. Using a proprietary dataset including archival data on professional German soccer players and clubs as well as survey data of more than 1,400 soccer fans, we find evidence for a positive effect of superstar characteristics and role model perception. We further find that players who measure up to the definition of a superstar are more important to fans of established teams than to fans of unsuccessful teams. The player's club tenure, however, seems to have no influence on fans' team identification. We argue that the effect of soccer stars on their fans is comparable to that of CEOs on their organizations' external stakeholders and consequently apply our results to the business domain. Our results contribute to organizational identification research by extending the list of determinants related to individual persons.
Keywords: L83; Z13; 330; Organizational identification; superstars; role model; fans; soccer